Practice in industry training in fish culture - Moyano, Simeona V. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1954)
This report is a summary of the fishculture activities during my practice-in-industry from April 1 to September 30, 1954, in Dagat-dagatan experimental fishery station, Malabonn, Rizal, and in the Pangasinan fishery school, Lucap, Alamines, Pangasinan and other stations like Calasiao, Mangatarem and Inigaran lakes of the same province. It is the aim of this report to show the fish culture activities based upon actual observations whether they are of the scientific or correct methods as compared with the theoretical knowledge about the industry.
Keywords: Fish-culture.